ISSUES OF INTEGRATION OF A PERSON INTO SOCIAL PROCESSES IN THE CONTEXT OF GLOBALIZATION AND DIGITAL TECHNOLOGIES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article analyzes the issues of integration of the individual into modern social processes from a philosophical, sociological and political perspective in the context of globalization, digital technologies, cultural diversity and post-industrial society. The study examines the transformational processes related to the social activity, identity and adaptation of the individual to national and universal values. On the basis of the analysis of foreign and local scientific sources, the mechanisms for ensuring the integration of the person, inter-institutional interactions and digital competencies in the conditions of New Uzbekistan are analyzed.